Faktor-Faktor Yang Mempengaruhi Kesehatan Jiwa Pada Remaja di Wilayah Kerja UPT Puskesmas Sambau - Ilda Nahar; Rachmawaty M. Noer; Mira Agusthia (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Mental health issues in adolescents should also be a major concern for the government. Mental health issues that can occur in adolescent life phases include Napza/Gadget abuse, peer pressure, school demands, disorientation and sexuality, media influence, risky sexual relationships and violent behavior.The risk of having a mental health disorder will be higher for children who often experience conflicting families, violence experienced by family members, and negative experiences. Bad environmental factors such as the influence of the Internet, negative experiences at home or in the school environment experienced by children can have a negative impact on their cognitive and emotional development. This research aims to identify the factors that affect mental health in teenagers in the UPT Puskesmas Sambau Working Area. This research design is quantitative descriptive with crossectional. The sample in this study is 10 to 18 years old teenagers who are in the UPT Puskesmas work area that have been detected have mental health problems of a total of 80 people using purposive sampling techniques. Analysis of this research data using chi-square. The results revealed that there was a relationship between family factors and mental health in adolescents in UPT Puskesmas Sambau with a p-value of 0,013. There was a relation between environmental factors and psychological health in teenagers in the UPT Sambau working area with a value of 0,036. Advice to health care can be helpful for routine screening of the child's development. In addition, children who are suspected of mental health disorders are expected to be referred to for examination and therapy.